Degradation of Verapamil hydrochloride in water by gliding arc discharge. (June 2016) - Krishna, Syam; Maslani, Alan; Izdebski, Tomasz; Horakova, Marta; Klementova, Sarka; Spatenka, Petr
Abstract: This study investigated the influence of gliding arc plasma discharge on the degradation of Verapamil hydrochloride in water. The plasma discharge was characterized by means of optical emission spectroscopy. Spectra of various atomic and molecular species were observed. Aqueous solution of Verapamil hydrochloride was exposed to gliding arc discharge operated in continuous discharge at atmospheric pressure and room temperature. The identification of Verapamil, the degradation mechanisms of Verapamil and its transformation products were performed using liquid chromatography – mass spectrometry (HPLC-MS). Experimental results indicate that the atmospheric pressure gliding arc plasma treatment has noticeable effects on Verapamil with satisfactory degradation efficiency. Plausible mechanisms of the degradation were discussed. Highlights: This is the first report of the degradation mechanism of Verapamil in water by gliding arc discharge. The presence of hydroxyl radicals in the gliding arc discharge was confirmed by optical emission spectroscopy. The degradation kinetics of Verapamil under gliding arc discharge was investigated.